2012
DOI: 10.1097/ncn.0b013e3182388921
|View full text |Cite
|
Sign up to set email alerts
|

Development and Pilot Test of a Culturally Sensitive CD-ROM for Hypertensive, Older Chinese Immigrants

Abstract: Hypertension control remains an issue for older Chinese immigrants because of the unique cultural health practices they use to manage their hypertension. Limited health education information on how to manage hypertension is available in Chinese. Because San Francisco has a large population of older Chinese immigrants, development of culturally sensitive educational material is important to help this population to achieve better blood pressure control. The purpose of this study was to develop and pilot test an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Video education is an effective education method that is used in several other fields of medical care. 11,12 However, because most Chinese glaucoma patients are elderly, they often have no Internet skills, and their decreased visual acuity directly affects their ability to benefit from health education. 5 The results suggested that health education with an ''audio accompanied with video experience'' encouraged active movement, balance, and better gait function, with superior results for the patients.…”
mentioning
confidence: 99%
“…Video education is an effective education method that is used in several other fields of medical care. 11,12 However, because most Chinese glaucoma patients are elderly, they often have no Internet skills, and their decreased visual acuity directly affects their ability to benefit from health education. 5 The results suggested that health education with an ''audio accompanied with video experience'' encouraged active movement, balance, and better gait function, with superior results for the patients.…”
mentioning
confidence: 99%
“…These consultations were reported to direct deep structure cultural sensitivity considerations for twenty-one of the studies included (88%). With the exception of three 32, 36, 42 studies (13%), the remaining involved stakeholders throughout the research process, and ten 25, 29, 31, 33, 36, 39, 4346 (42%) of the project researchers collaborated with stakeholders. Only two 29, 33 studies (8%) informed their stakeholders about the research process, and another two 39, 44 (8%) provided support to stakeholders for implementation and dissemination of the KMb product.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve deep structure contextualization authors most commonly consulted specific end-user populations (e.g. clinical populations [21%, n=5], 25,[29][30][31][32] community members [17%, n=4] 24,27,33,34 through focus groups (13%, n=3), 28,35,36 and assessed various cultural contexts (33%, n=7). 26,[37][38][39][40][41]…”
Section: Approach and Type Of Adaptationmentioning
confidence: 99%